Cardiovascular disease risk factors and cognitive functions in older Russian adults. (14th October 2021) - Titarenko, A V; Shishkin, S V; Shcherbakova, L V; Verevkin, E G; Shapkina, M Y U; Hubacek, J A; Bobak, M; Malyutina, S K; ,
Abstract: Background: The prevalence of cardiovascular diseases (CVD) is increasing due to the global trend towards an aging population. CVD and cerebrovascular disease have a negative impact on cognitive health, and CVD risk factors may also be associated with cognitive decline with aging. Purpose: To investigate associations of modifiable risk factors for CVD with cognitive functions (CF) in older Russian adults. Methods: A random population sample (3153 men and women, aged 55–84 years) was examined in our city in the 3rd wave of the Russian arm of the international project HAPIEE (Health, Alcohol, and Psychosocial Factors in Eastern Europe). We used standardized epidemiological and instrumental methods for assessment of risk factors, history and treatment of CVD. Cognitive tests included the assessment of memory indicators (immediate and delayed recall), semantic verbal fluency (animal naming), attention, concentration and processing speed (letter cancellation task). Associations between CVD risk factors and cognitive indices were analyzed cross-sectionally. Results: Mean age in men was of 69.2±7.0 years (n=1198), in women - 69.7±6.9 (n=1955). In both sexes all cognitive domains were positively associated with education and negatively with age (p<0.001 for all cases). In men, after adjusting for health and lifestyle conditions, systolic blood pressure had inverse association with semantic verbal fluency (p=0.015); level of plasma glucose (p=0.003), waist-to-hip ratio (p=0.013) and smoking (p=0.028) were negative associated with letter cancellation task. In multivariate analyses in women, frequency of alcohol consumption (p<0.001 for all CF) and total cholesterol (p=0.042 for memory scores; p=0.001 for letter cancellation task) had positive relationship with CF indices, waist-to-hip ratio (p=0.002 for memory scores, p=0.038 for semantic fluency), level of plasma glucose (p=0.002 for memory scores, p<0.001 for letter cancellation task) and smoking (p<0.001 for letter cancellation task) had inverse relationships with cognition. Conclusion: Our results show that metabolic risk factors (systolic blood pressure, plasma glucose, waist-to-hip ratio) and smoking had inverse relationship with CF indices in both sexes, and the level of blood lipids (total cholesterol and high-density lipoprotein cholesterol) and frequency of alcohol consumption (more pronounced in women) had positive associations with cognitive domains. These associations were independent from age. In multivariate analyses, some of these correlations were attenuated, and most associations were at least partly mediated by education. These findings highlight the importance of managing CVD risk factors to prevent cognitive decline. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian Foundation for Basic Research (20-313-90016), Russian Academy of Sciences (AAAA-A17-117112850280-2)